Glycerol hyperhydration to beat the heat? - Robergs, R.
Extra water ingested with glycerol is held in the body for several hours and may enhance performance by a few percent in events lasting more than an hour in hot and humid conditions. Headaches, blurred vision, and stomach upsets are side effects for some athletes who take too much too quickly. More research is needed to determine whether adequate intake of a sports drink containing salt and carbohydrate gives similar gains in performance.